Analysis of Methyldopa Therapy on sFlt-1 Antiangiogenic Levels in Patients with Severe Preeclampsia - Herwati, Teri Wina; Yulistiani, Yulistiani; M, Eddy Zarkaty (Folia Medica Indonesiana, 2018)
Methyldopa is the first-line drugs to treat hypertension in pregnancy. It can decrease blood pressure in preeclampsia by affecting a2-adrenoreceptors in central nervous system. However, it could also act by decreasing production of sFlt-1 antiangiogenic protein levels involved in the pathophysiology of hypertention in preeclampsia. The purpose of this study was to analyze methyldopa therapy on sFlt-1 antiangiogenic levels in the plasma of pregnant women with severe preeclampsia at the Obstetric Departement, Haji Hospital, Surabaya. This was a prospective study with observational cross-section study design. The sFlt-1 angiogenic levels were observed before and after (48 hours) methyldopa administration in severe preeclampsia patient with or without complications in the period of August to October 2016. Patient received methyldopa 250 mg or 500 mg, three times a day for clinical indications according a standard protocol. The study was approved by the ethical committee of Haji Hospital, Surabaya. There were 19 patients with preeclampsia who met the inclusion criteria, showed a decrease in the levels of sFlt-1 before and 48 hours after methyldopa therapy. Levels of sFlt-1 before methyldopa therapy in a dose of 250 mg was 10.15±10.00 (2.55-34.70) ng/ml and after therapy 8,37±9,20 (0.72-9.20) ng/ml, with a percentage decrease 17.54%. sFlt-1 levels before methyldopa therapy in a dose of 500 mg was 8.05±7.07 (2.55-20.76) ng/ml, after therapy 4.50±2.90 (2.19-9.95) ng/ml, with a percentage decrease 44.16%. Methyldopa therapy could decrease sFlt-1 levels of antiangiogenic factor in patients with severe preeclampsia.